Early Experience with Bilateral Internal Mammary Artery Grafting - Khan, Ghufranullah; Hassan, Sulaiman B (Journal of Postgraduate Medical Institute, 2011)
We carried out first bilateral internal mammary artery grafting in March 93 and ever since the number of patients receiving bilateral internal mammary artery grafts has constantly grown. This study is a review of first 10 patients who were operated between March 93 to August 95. Age ranged froom 35 - 47 and the median age was 45 diabetes were excluded. All the operations were elective in nature. All patients received additional saphenous vein grafts. 3 patients had sequential LIMA grafts constructed between diagonal and LAD. There was no mortality and 8 patients made uneventful recovery. One patients developed perioperative MI and required balloon pump support, and two required reopening . None of the patients requried inotropic support. No sternal wound problems occured. In conclusion bilateral internal mammary artery grafting does not increase surgical risk and wound infection is not a problem if diabetics are excluded.